European Heart Rhythm Association (EHRA) international consensus document on how to prevent, diagnose, and treat cardiac implantable electronic device infections—endorsed by the Heart Rhythm Society (HRS), the Asia Pacific Heart Rhythm Society (APHRS), the Latin American Heart Rhythm Society (LAHRS), International Society for Cardiovascular Infectious Diseases (ISCVID), and the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) in collaboration with the European Association for Cardio-Thoracic Surgery (EACTS). (26th February 2020) - Blomström-Lundqvist, Carina; Traykov, Vassil; Erba, Paola Anna; Burri, Haran; Nielsen, Jens Cosedis; Bongiorni, Maria Grazia; Poole, Jeanne; Boriani, Giuseppe; Costa, Roberto; Deharo, Jean-Claude; Epstein, Laurence M; Sághy, László; et al.
Abstract: Pacemakers, implantable cardiac defibrillators, and cardiac resynchronization therapy devices are potentially lifesaving treatments for a number of cardiac conditions but are not without risk. Most concerning is the risk of a cardiac implantable electronic device (CIED) infection, which is associated with significant morbidity, increased hospitalizations, reduced survival, and increased health care costs. Recommended preventive strategies such as administration of intravenous antibiotics before implantation are well-recognized. Uncertainties have remained about the role of various preventive, diagnostic, and treatment measures such as skin antiseptics, pocket antibiotic solutions, antibacterial envelopes, prolonged antibiotics post-implantation, and others. When compared with previous guidelines or consensus statements, the present consensus document gives guidance on the use of novel device alternatives, novel oral anticoagulants, antibacterial envelopes, prolonged antibiotics post-implantation, as well as definitions on minimum quality requirements for centres and operators and volumes. The recognition that an international consensus document focused on management of CIED infections is lacking, the dissemination of results from new important randomized trials focusing on prevention of CIED infections, and observed divergences in managing device-related infections as found in an European Heart Rhythm Association worldwide survey, provided a strong incentive for a Novel 2019 International State-of-the-art Consensus document on risk assessment, prevention, diagnosis, and treatment of CIED infections.